(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
This article delves into the emerging role of facial recognition technology in demographic research, highlighting both its transformative potential and the challenges it presents. The author explores how facial recognition can enhance the accuracy and efficiency of demographic studies by enabling more precise identification and categorization of individuals across different age, gender, and ethnic groups. The article underscores the opportunity for more targeted applications in fields such as healthcare, marketing, and urban planning